Pengaruh Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Muhyi Bazana Putra - Muhammad Badri Annury; Syahrum Agung; Widhi Ariyo Bimo (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
This study aims to determine the effect of leadership and work motivation on employee performance at PT. Muhyi Bazana Putra with a sample of 53 respondents. The method used is a quantitative approach by distributing questionnaire research instruments to employees which are processed using a computer application. This study was conducted at PT. Muhyi Bazana Putra. The variables of leadership (X1) and work motivation (X2) on employee performance (Y) are processed using correlation analysis, regression analysis, t-test, F-test and coefficient of determination. The results of the study using the t-test indicate that the leadership variable (X1) has no effect but is significant on employee performance (Y) and the work motivation variable (X2) has an effect and is significant on employee performance (Y). While the F test shows that leadership (X1) and work motivation (X2) together have an effect and are significant on employee performance (Y). The Adjusted R square value is 0.459 or 45.9% which means that the leadership and work motivation variables can explain the changes that occur in employee performance variables, by 45.9% and the remaining 54.1% is explained by other variables that are not studied.